Voice of fear ebook - Graham, Heather (Krewe of Hunters, 2022)
A killer is looking to silence them, once and for all. FBI agent Jordan Wallace is close to cracking the human trafficking case she's been working, when she does the one thing she should never do: let her guard down. The botched undercover mission is semisalvaged by the last-minute appearance of criminal psychologist Patrick Law, but Jordan can't imagine making a worse first impression. Especially when she's partnered with Patrick moving forward. Patrick's innate ability to get inside a criminal's head is an asset for the Krewe of Hunters. But Jordan wishes she could protect her own thoughts from her new partner. Patrick assures her that both she and her thoughts are safe with him, but Jordan's less sure about her heart. Letting someone have her back has never been her strong suit, but with a dangerous killer still at large, trusting in Patrick might be the only thing keeping them alive. "A harrowing journey... Intelligent, fast-paced and frightening at all times." —Suspense Magazine on The Final Deception Krewe of Hunters Book 1: Phantom Evil Book 2: Heart of Evil Book 3: Sacred Evil Book 4: The Evil Inside Book 5: The Unseen Book 6: The Unholy Book 7: The Unspoken Book 8: The Uninvited Book 9: THE NIGHT IS WATCHING Book 10: The Night Is Alive Book 11: THE NIGHT IS FOREVER Book 12: The Cursed Book 13: The Hexed Book 14: The Betrayed Book 15: The Silenced Book 16: The Forgotten Book 17: The Hidden Book 18: Haunted Destiny Book 19: Deadly Fate Book 20: Darkest Journey Book 21: Dying Breath Book 22: Dark Rites Book 23: Wicked Deeds Book 24: Fade to Black Book 25: Pale as Death Book 26: Echoes of Evil Book 27: The Summoning Book 28: The Seekers Book 29: The Stalking Book 30: Seeing Darkness Book 31: Deadly Touch Book 32: Dreaming Death Book 33: The Unforgiven Book 34: The Forbidden Book 35: The Unknown Book 36: Sound of Darkness Book 37: Aura of Night Book 38: Voice of Fear Don't miss New York Times bestselling author Heather Graham's next thrilling read, SHADOW OF DEATH!